The dilemma of national security and international cooperation in outer space: space technology trade and proliferation controls and their impact on global civil space cooperation - Mineiro, Michael (McGill University, 2011)
In this thesis space technology trade and proliferation controls are analyzed, focusing on two substantive issues that illustrate the challenges and opportunities of reform. The first substantive issue examined is the challenge of domestic law and policy reform in light of international regulatory divergence. This issue is examined through a case study of the U.S. commercial communication satellite export control regime. The second issue is the international implications of space technology trade and proliferation control on global civil space cooperation. The unifying demonstration of this doctoral thesis is that States operate in an international legal system that perpetuates a self-justified security dilemma whose basis originates in the sovereign legal right of States to produce, procure, and maintain space technologies of a military nature. As a result, the international legal system governing space technology trade and proliferation creates a tension between perceived national security needs and the benefits of global cooperation.